Rwanda Diagnostic Review of Consumer Protection and Financial Literacy : Volume 2. Comparison with Good Practices - World Bank (World Bank, Washington, DC, 2017)
Although the Parliament of Rwanda has passed an impressive array of financial sector laws since 2008, the laws relevant to financial consumer protection are very limited and in some cases overlapping. Consumer protection in Rwandan banking, microfinance, and insurance sectors is fragmented because of insufficiently defined roles and responsibilities among institutions and unclear enforcement capacity. While there are some strong provisions in some areas such as electronic money transfer, electronic transmission, credit information, and market conduct regulation in the insurance industry, many other areas are lagging. Rwandan authorities recognize that a sound financial consumer protection framework is fundamental to improving usage and quality of financial services, access to them, and overall deepening of the financial sector. This World Bank diagnostic review was requested by the National Bank of Rwanda (BNR) in November 2012. Modules on banking and microfinance sectors were developed based on publicly available information and data during the World Bank mission in Rwanda, and the review of the insurance sector was conducted through a desk review using the data obtained from BNR data requests and questionnaires, and the analysis is therefore constrained by it. Volume I of the review summarizes its key findings and recommendations, and volume II provides a detailed assessment against the World Bank’s good practices on financial consumer protection.